设函数[img=277x61]180350777e64a42.png[/img],求[img=34x25]18035077877aff8.png[/img]的反函数。
A: [img=307x83]180350779216117.png[/img]
B: [img=297x83]180350779c32060.png[/img]
C: [img=297x83]18035077a76574a.png[/img]
D: [img=307x83]18035077b23af3b.png[/img]
A: [img=307x83]180350779216117.png[/img]
B: [img=297x83]180350779c32060.png[/img]
C: [img=297x83]18035077a76574a.png[/img]
D: [img=307x83]18035077b23af3b.png[/img]
举一反三
- 设函数[img=277x61]18035075d262d8f.png[/img],求[img=34x25]18035075db7250b.png[/img]的反函数。 A: [img=307x83]18035075e6011cf.png[/img] B: [img=297x83]18035075f082dd5.png[/img] C: [img=297x83]18035075fab88bf.png[/img] D: [img=307x83]1803507605b0788.png[/img]
- 设函数[img=277x61]180350777e64a42.png[/img],求[img=34x25]18035077877aff8.png[/img]的反函数。 未知类型:{'options': ['', '', '', ''], 'type': 102}
- 设(X,Y)的分布函数为[img=549x53]18031e937a7b053.png[/img]则(X,Y)关于X的边缘分布函数FX(x) = ( ). A: [img=287x55]18031e93855481e.png[/img] B: [img=285x52]18031e93918b0ca.png[/img] C: [img=296x55]18031e939bc0749.png[/img] D: [img=294x56]18031e93a5c4883.png[/img]
- 设(X,Y)的分布函数为[img=549x53]1803a74a8f6ca05.png[/img]则(X,Y)关于X的边缘分布函数FX(x) = ( ). A: [img=287x55]1803a74a9a08d05.png[/img] B: [img=285x52]1803a74aa4ac3b9.png[/img] C: [img=296x55]1803a74aae81937.png[/img] D: [img=294x56]1803a74ab8d5dc7.png[/img]
- 设(X,Y)的分布函数为[img=549x53]1802f2b06f71f92.png[/img]则(X,Y)关于X的边缘分布函数FX(x) = ( ). A: [img=287x55]1802f2b07b2935e.png[/img] B: [img=285x52]1802f2b085d42f7.png[/img] C: [img=296x55]1802f2b0909ff33.png[/img] D: [img=294x56]1802f2b09a4b182.png[/img]